Vasala Sutta Sebagai Kritik Sosial: Landasan Etika Humanistik Dalam Buddhisme - Bondan Ade Prasetya (Sekolah Tinggi Agama Buddha Maha Prajna Jakarta, 2026)
This study aims to analyze the Vasala Sutta as a form of social criticism and to identify the foundations of humanistic ethics within Buddhist teachings that are relevant to the phenomenon of social discrimination based on status and identity. This research employs a descriptive qualitative approach using a library research method, utilizing primary data in the form of the Vasala Sutta text and secondary data derived from indexed scientific journal articles. Data collection techniques are conducted through documentation and systematic literature review, with sources selected using purposive sampling based on relevance and academic credibility. The results indicate several key themes, namely the deconstruction of socially constructed identity based on birth, the affirmation of morality as the primary indicator of human value, criticism of discriminatory social structures, the internalization of humanistic values, and the relevance of these teachings in the context of modern society. These findings demonstrate that the Vasala Sutta embodies principles of moral equality and a critique of the caste system, which can be understood as the foundation of humanistic ethics in Buddhism. In conclusion, this study contributes theoretically to enriching the study of Buddhist ethics through a socio-humanistic perspective, as well as providing practical implications for the development of inclusive values in education and multicultural societies. This study also recommends further research using empirical approaches to explore the implementation of these values in contemporary social contexts.